Why are immigrants' incarceration rates so low? evidence on selective immigration, deterrence, and deportation - Anne Morrison Piehl
Much of the concern about immigration adversely affecting crime derives from the fact that immigrants tend to have characteristics in common with native born populations that are disproportionately incarcerated. This perception of a link between immigration and crime led to legislation in the 1990s increasing punishments toward criminal aliens. Despite the widespread perception of a link between immigration and crime, immigrants have much lower institutionalization (incarceration) rates than the native born. More recently arrived immigrants have the lowest comparative incarceration rates, and this difference increased from 1980 to 2000. We present a model of immigrant self-selection that suggests why, despite poor labor market outcomes, immigrants may have better incarceration outcomes than the native- born. We examine whether the improvement in immigrants’ relative incarceration rates over the last three decades is linked to increased deportation, immigrant self- selection, or deterrence. Our evidence suggests that deportation and deterrence of immigrants’ crime commission from the threat of deportation are not driving the results. Rather, immigrants appear to be self-selected to have low criminal propensities and this has increased over time.Immigrants ; Deportation